Primary desmoplastic small-round-cell tumor of the ovary - Ahmed Atef; Khaled Gaballa; Mohammad Zuhdy; Khalid Atallah; Wagdi Elkashef; Shadi Awny; Basma Gadelhak; Basel Refky (Journal of the Egyptian National Cancer Institute, 2019)
Abstract Background Desmoplastic small-round-cell tumor (DSRCT) is an extremely rare and highly aggressive malignancy. It is of yet unclear origin, but it is assumed to be of a mesothelial origin based on its tendency for widespread metastasis in serosal linings. Case presentation In this report, we describe a young female who presented with bilateral ovarian masses that mimicked the classic clinical picture of ovarian cancer. The patient had a cytoreductive surgery done in the form of total abdominal hysterectomy, bilateral salpingo-oophorectomy, omentectomy, pelvic peritonectomy, low para-aortic and bilateral iliac lymphadenectomy. Postoperative course was smooth with no adverse events. The final pathology report revealed desmoplastic small-round-cell tumor. Afterwards, the patient was referred to medical oncologist to receive her adjuvant therapy. Conclusions DSRCT is still an unknown disease to us given the limited number of cases and poor survival. Given the lack of clear guidelines, treatment is offered based on the best available evidence and the collaborative effort of a multi-disciplinary team.